THE CHALLENGES OF SCIENCE TEACHERS IN IMPROVING STUDENTS’ RATIONAL THINKING ABILITIES THROUGH SOCIOSCIENTIFIC ISSUE BASED LEARNING - Anggi Sofiana, Karisma; Arif, Syaiful (INSECTA: Integrative Science Education and Teaching Activity Journal, 2024)
Reasoning is one of the cognitive abilities developed to gain knowledge. Students must have the ability to reason so that they can solve a problem through common sense. They can see accurate information. However, in most communities, many myths or issues are spread among the public, some of which are not even true, so it would be better if science learning were connected to socioscientific issues. This research aims to explore the challenges of junior high school teachers in improving students' rational thinking abilities when they design and facilitate learning of socioscientific issues in the classroom. This research was conducted at SMPN 1 Mlarak with research samples, namely science teachers at SMPN 1 Mlarak Ponorogo and class 7C students at SMPN 1 Mlarak. This research uses a qualitative approach, applying in-depth interview and observation methods. This research uses the N VIVO application to analyze data. From this research, the results showed that several things were challenges for teachers in improving students' rational thinking abilities through socioscientific issue-based learning, namely students' abilities, limited time, and difficulty finding relevant examples. Knowing the challenges teachers face in teaching provides an idea of finding the right solution to overcome the problems.